Itaconate Production from Crude Substrates with U. maydis: Scale-up of an Industrially Relevant Bioprocess - Tabea Helm; Thilo Stausberg; Martina Previati; Philipp Ernst; Bianca Klein; Tobias Busche; Jörn Kalinowski; Daniel Wibberg; Wolfgang Wiechert; Lien Claerhout; Nick Wierckx; Stephan Noack (Microbial Cell Factories, 2024)
Abstract Background Industrial by-products accrue in most agricultural or food-related production processes, but additional value chains have already been established for many of them. Crude glycerol has a 60% lower market value than commercial glucose, as large quantities are produced in the biodiesel industry, but its valorisation is still underutilized. Due to its high carbon content and the natural ability of many microorganisms to metabolise it, microbial upcycling is a suitable option for this waste product. Results In this work, the use of crude glycerol for the production of the value-added compound itaconate is demonstrated using the smut fungus Ustilago maydis. Starting with a highly engineered strain, itaconate production from an industrial glycerol waste stream was quickly established on a small scale, and the resulting yields were already competitive with processes using commercial sugars. Adaptive laboratory evolution resulted in an evolved strain with a 72% increased growth rate on glycerol. In the subsequent development and optimisation of a fed-batch process on a 1.5-2 L scale, the use of molasses, a side stream of sugar beet processing, eliminated the need for other expensive media components such as nitrogen or vitamins for biomass growth. The optimised process was scaled up to 150 L, achieving an overall titre of 72 g L− 1, a yield of 0.34 g g− 1, and a productivity of 0.54 g L− 1 h− 1. Conclusions Pilot-scale itaconate production from the complementary waste streams molasses and glycerol has been successfully established. In addition to achieving competitive performance indicators, the proposed dual feedstock strategy offers lower process costs and carbon footprint for the production of bio-based itaconate.